(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The oriented strand board (OSB) is a relatively modern type of engineered wood product used broadly in construction industry and the furniture production. An essential structural parameter of the OSB plate is the orientation of the layering strands (flakes) in the 3-D space XYZ, which pre-determines significant diversity in the directional strength of the final material. A structural model of a 3-layered OSB is presented and the parameters of the morphological structure are analyzed. Optimal limits of the principal morphology criteria ratios are established and optimized dimensions of the flakes are recommended. An empirical equation for calculating the bending strength of the manufactured composite plates is derived. In conclusion, an average value of the principal ratio RE = Eb ׀׀ / Eb ⊥= σb ׀׀ / σ0 ⊥= 2,25 is suggested, that could be used in the OSB production.